Case report of non-gene editing CD7 CAR T cell therapy in CD7+ Sézary syndrome: preclinical validation and first-in-human use - Xu, Haichan; Sun, Lihua; Wu, Zehua; DeStefano, Vincent M.; Wada, Masayuki; Chow, Jennifer E.; Yi, Hui; Wang, Guoling; Dai, Jing; Zheng, Wei; Wang, Ting; Zhang, Wenli; et al. (Frontiers in Immunology, 2025)
IntroductionSézary syndrome (SS) is a leukemic form of cutaneous T cell lymphoma (CTCL), distinguished from mycosis fungoides by the presence of cancerous lymphocytes in the blood and often bears very poor prognoses. SS treatment is palliative, and thus novel therapies are needed. The CD7 surface antigen is highly expressed and confined to the surface of T cells, therefore when present, serves as a promising target for immunotherapy.MethodsHerein we describe the preclinical validation and clinical application of our non-gene editing CD7 targeted chimeric antigen receptor (CAR) T therapy to treat relapsed/refractory (r/r) CD7 expressing SS. The CD7 CAR construct possesses a “safety switch” (RTX) to enable rapid depletion of the CAR T treatment with administration of rituximab. Preclinical evaluation of the CD7-RTX CAR T cells demonstrated >99% depletion of target cells in both co-cultures, at 1:1 and 2:1 effector: target (E:T) ratios, and mouse models. In a mouse model, “safety switch” testing resulted in rapid elimination of CAR T cells with rituximab infusion. RTX, in our CD7 therapy, has not yet been clinically validated.ResultsA 53-year-old male diagnosed with r/r SS, expressing CD7, was treated with 2×106 CD7-RTX CAR T cells/kg of body weight, as compassionate use. The patient achieved medication and symptom free complete remission (CR) within 28 days post-CAR. The patient remained in CR at 18-month follow-up. The treatment was well tolerated and without severe adverse events (SAEs).DiscussionOur CD7-RTX CAR T therapy demonstrates exceptional safety and efficacy in one patient with CD7+ r/r SS. This was the first recorded use of CD7 targeted CAR T therapy to treat SS. SS is prototypically CD7-, thus despite its efficacy in this patient, this treatment approach is likely not generalizable to most SS patients. However, this study supports the importance of thorough tumor characterization and the potential use of CD7-RTX CAR T cells to treat a variety of malignancies expressing CD7. Future clinical trials are required to characterize the safety and efficacy of CD7-RTX CAR T cells.